Analisis Peran Auditor Internal dalam Meningkatkan Kinerja Organisasi pada Rumah Sakit Muhammadiyah Bandung - Muhammad Rafi Habiburrahman; Iyeh Supriatna (Indonesian Accounting Literacy Journal, 2020)
Internal auditor function as supervisors to ensure internal activities are adequate and implemented in accordance with established management policies, and consequently the internal auditors expected to improve organization performance. Muhammadiyah Bandung Hospital is one of the hospitals that received paripurna accreditation assessment. However, that assessment must still be maintained and improved. For this reseach aims to examine how much the role of internal auditors in improving organization performance. The research method used is descriptive qualitative and data collection techniques using interviews, observation, and documentation. The results of this reseach can be concluded that the role of the Satuan Pemeriksaan Internal (SPI) in improving organizational performance at Muhammadiyah Hospital Bandung is good because it covers all parts and its implementation is in accordance with standards, and also indirectly the SPI unit helps in increasing accreditation assessments. However, there are several important things that are still not fulfilled by the SPI unit to improve the role of the internal auditor.